Penerapan Metode Ta’zir sebagai Upaya untuk Meningkatkan Kedisiplinan Santriwati - Shelly Selvia; Sutopo Sutopo (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
Sunan Drajat Islamic Boarding School Paciran Lamongan, East Java, is a non-formal education that aims to form virtuous people, have good morals, and fear Allah SWT. Discipline plays an important role in the educational process so that female students can be responsible and have more self-control in developing obedience to the rules that have been set. Discipline is also a means to shape, control and create a person's behavior patterns. Therefore, in the process of increasing discipline applied in Islamic boarding school education. The ta'zir method has a positive impact and has a big impact on female students to be more disciplined and more able to obey the rules that have been set. The results of this study can be concluded that after the implementation of the ta'zir method, many female students feel deterred from violating the rules. Various forms of ta'ziran include light, medium, heavy. Ta'ziran is given according to the violations committed by the female students, such as sweeping the dormitory, taking out the trash, cleaning the bathroom. The ta'zir method applied has a positive impact and has a major impact on female students, making female students more disciplined and obedient to the rules.